Overall manifestations and survival of pediatric patients with Langerhans cell histiocytosis. A middle-income country (mic) national multicenter study - Liliana Velasco-Hidalgo; Alejandro González-Garay; Roberto Rivera-Luna; Marta M. Zapata-Tarrés; Cesar Galván-Diaz; Araceli López-Facundo; Farina Arreguín-González; José León-Espitia; Daniel Ortiz-Morales; Luis Juárez-Villegas; Oscar González-Llano; Daniela Covarrubias-Zapata; et al. (Permanyer, 2024)
Background: Langerhans cell histiocytosis (LCH) is a rare neoplastic disease characterized by clonal proliferation of dendritic cells. It is Mexico's ninth most frequent malignancy in patients under 18 years of age. The aim of the study was to determine the clinical characteristics, treatment, and survival of Mexican pediatric patients diagnosed with LCH treated from January 2010 to December 2018. Methods: We conducted a retrospective study of LCH using data from 19 accredited hospitals throughout the Mexican Republic. Patients < 18 years who were diagnosed with LCH between January 2010 and December 2018 were included (253 patients) in the study. Results: All patients had a histopathological diagnosis, and extension studies were performed at their treatment centers. The median age at diagnosis was 19 months. The most frequently affected sites included the bone (178 cases; 70%) and the skin (131 cases; 51.7%). Of the patients in Group 1, 48 (42%) had bone marrow involvement, 62 (53%) had splenomegaly, and 39 (34.8%) had liver involvement. Of the patients who underwent chemotherapy treatment, 61.2% exhibited a complete response, and 36 patients (14.2%) relapsed after complete remission. The most frequent sites of relapse were the skin, bone, lymph nodes, and liver. The overall survival rate was 91.3% and was lower for patients in Group 1 (77%) compared with those in Groups 2 (97%) and 3 (100%), p = 0.001. Conclusion: The current report aims to demonstrate the findings of a multicenter study conducted on Mexican children with LCH; consequently, these treatment results for a relatively infrequent disease merit further research.